أسباب التشققـات في المنشـآت الخرسانية المسلحة، وبعض طرق المعالجــــة. - ملحم, عصام (Latakia University Journal -Engineering Sciences Series, 2016)
إذا لم يكن متشققاً فإنه لا يعمل. إن هذه العبارة نتيجة حتمية لعدم تساوي مقاومة الشد للخرسانة، مع مقاومة الشد للفولاذ في عناصر المنشآت الخرسانية، والمصممة بشكل اقتصادي.وبالرغم من ذلك فإنه نادراً ما يستخدمها المهندس المصمم لتبرير حادثة تشقق في مبنى، وقد يستخدمها لتهدئة صاحب منشأ متشقق. لهذا كان علينا أن نحدد التشققات المقبولة ودرجة قبولها.ويعد ظهور التشققات في المنشآت الخرسانية، والخرسانية المسلحة، دلالة مرضية على الرغم من أن بعض أنواع هذه التشققات لا يبدي تأثيراً سلبياً على عمل المنشأة من وجهة نظر المتطلبات الاستثمارية.إن أسباب التشققات كثيرة ومتنوعة، وقد يظهر أحدها في عدة أنماط تشقق وقد تؤدي عدة أسباب إلى نوع واحد من التشقق.إن تشكل التشققات في الخرسانة يختلف باختلاف العوامل المؤدية له، وهذه العوامل قد تكون إنشائية أو استثمارية. من الصعب وضع قائمة مفيدة للأسباب المحتملة للتشقق، حيث إنها تحوي عدة أشكال ويمكن لأيَ منها أن يزيد خطورة الآخر أو يتجاوزه، ولإظهار العلاقة بين هذه الأشكال من ناحية أخر نقترح شجرة التشقق، التي قد تساعد المصمم في وضع الأسباب المحتملة للتشقق في مخيلته.إن المميزة الرئيسة للتشققات أن عقدها الثلاث تحدد المراحل التاريخية الثلاث لحياة المنشأ: مراحل التصميم والإنشاء والخدمة، وتقسم إلى قوائم، الأسباب المولدة للشقوق وتأثيرها في بعضها بعضا.تفرع الشجرة عند مرحلة التشقق إلى جذور الشد ومقاومة الخرسانة للشد. علماً أن الفروع الأولى تحدد الخواص الفيزيائية للشقوق (اتساعها، عمقها، طولها،...) وتشق طريقها عبر المراحل الثلاثة، (ويمثل تقييد الحركة أهم هذه الفروع). حتى ينجلي النمو عن مجموعة من السوق(ساق النبات)الطرفية، والتي يمكن أن تحدد خطورة التشقق، حيث تسبب مشاكل تتعلق بالديمومة والناحية الجمالية، وقد تحتاج إلى دراسة دقيقة وإصلاح. إن هدف هذا البحث هو دراسة أسباب حدوث التشققات والعوامل التي تؤدي لزيادتها، وإلى أشكال انتشار التشققات في مختلف العناصر الهندسية (أعمدة، جوائز، بلاطات...)، وما هي الإجراءات المتخذة لمنع، أو للحد من ظهور هذه التشققات. كما يتطرق البحث إلى أحدث الطرق وأفضل المواد المستخدمة في ترميمها.If it is not cracked then it is not working. This statement is the actual result of difference between tension strength of concrete and tension strength of steel in concrete structures elements that are economically designed. In spite of that, engineers rarely use this statement to explain cracks in buildings, but sometimes they use it to calm down the owner of some cracked building. That's why we should define acceptable cracks and their degrees.Cracks in concrete and reinforced concrete structures are a bad sign, although some of these cracks have no negative effect on the utilization of the structure.Reasons of cracks are various and different, some of them might occur in different types of cracking while others may lead to a single type of crack.Cracks formation in concrete varies due to the different factors causing them, which also may be structural or related to the utilization of building.It is not easy to put a useful list for probable reasons of cracking as cracks have many shapes and any one of them might increase the danger of another one or even exceeds it. To explain the relationship between these types, we proposed the cracking tree, which may help the designer to take into consideration the probable reasons for cracking. The main specification of cracks is that its three nodes define the three periods in the life of a structure: design, construction and service. These are also divided into lists including reasons causing cracking and their effects on each other.Cracking tree branches into tension roots, taking into consideration that the first branches determine the physical properties of cracks (width, depth, length,…). Then these branches take their way throughout the three phases,(restriction of movement is the most important branch). When these branches stop growing, they can tell the severity of cracking, in respect to durability and beauty. This definitely still needs accurate study and repair.This research aims to study the direct reasons of cracking, factors that increase cracks, and types of cracking growing in structural members (Columns, Beams, Plates,..). Add to that the procedures needed to prevent or stop cracks growing. We also offer an attempt to point the best methods and materials to be used for restoration.